LIKUIDITAS, PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013 – 2017) - Inna Fachrina Yuliana; Djoko Wahyudi (Faculty of Economic and Business Universitas STIKUBANK, 2018)
This study examines the effect of liquidity, profitability, leverage, firm size, capital intensity and inventory intensity on tax aggressiveness. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the period 2013 - 2017. The sample in this study uses 315 data of manufacturing companies listed on the Indonesia Stock Exchange for the period 2013 - 2017 using the purposive sampling method. The analytical tool used is normality test, classic assumption test, multiple linear regression test, model test and hypothesis test. The results of the study show that liquidity, company size, capital intensity, inventory intensity affect the tax aggressiveness. While profitability and leverage have no effect on tax aggressiveness. Keywords: liquidity, profitability, leverage, company size, capital intensity, inventory intensity and tax aggressiveness